"Invisible Killer": Seasonal Allergies and Accidents - Mika Akesaka; Hitoshi Shigeoka (Institute of Labor Economics (IZA), 2023)
Although at least 400 million people suffer from seasonal allergies worldwide, the adverse effects of pollen on "non-health" outcomes, such as cognition and productivity, are relatively understudied. Using ambulance archives from Japan, we demonstrate that high pollen days are associated with increased accidents and injuries— one of the most extreme consequences of cognitive impairment. We find some evidence of avoidance behavior in buying allergy products but limited evidence in curtailing outdoor activity, implying that the cognitive risk of pollen exposure is discounted. Our results call for governmental efforts to raise public awareness of the risks and promote widespread behavioral change.
Keywords: I12; J24; Q51; Q53; Q54; 330; seasonal allergies; pollen; accidents; cognition; avoidance behaviors; adaptation; climate change